2014
DOI: 10.15408/ijee.v1i2.1303
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Technology in Efl Classroom

Abstract: In  response  to  an  appeal  from  Indonesia’s  Ministry  of  Education  and  Culture  to  all universities and colleges to improve the quality of tertiary  education toward regional and international standard, language institutions are making great efforts to further promote the  foreign  language  learning  process.  In  the  last  few  years  there  have  been  dramatic changes  in  the  ways  that  languages  are  taught  by communicative  approach  and  the introduction of technological tools. In recent … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
13
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 8 publications
2
13
0
Order By: Relevance
“…This statement showed that ICT can be used as a resource provided several English materials. It is in line with the statement of Haswani (2014) that ICT provides accesses to authentic materials. For example, the English teachers are able to deliver authentic materials such as videos and podcast from internet and then the students can assess their language skills by listening and observing body languages of native speakers (Cakici, 2016;Otero, 2016).…”
Section: Classroomsupporting
confidence: 86%
See 1 more Smart Citation
“…This statement showed that ICT can be used as a resource provided several English materials. It is in line with the statement of Haswani (2014) that ICT provides accesses to authentic materials. For example, the English teachers are able to deliver authentic materials such as videos and podcast from internet and then the students can assess their language skills by listening and observing body languages of native speakers (Cakici, 2016;Otero, 2016).…”
Section: Classroomsupporting
confidence: 86%
“…It is in line with the statement of Parvin and Salam (2015) that ICT plays a role in the language classroom changing to be more innovative learning. Besides, ICT as a tool facilitates the students to learn English language and as a source provides access to authentic materials and the information that can supplement students' learning experiences (Ammanni & Aparanjani, 2016;Fatimah & Santiana, 2017;Haswani, 2014). Then, Ammanni and Aparanjani (2016) and Stockwell (2013) state that ICT is able to enhance students' motivation in learning English language.…”
Section: The Roles Of Ict In English Teachingmentioning
confidence: 99%
“…Researchers focused on the importance of using technology in EFL learning to help and improve language learning. Technology enables teachers to adapt classroom activities, thus enhancing the language learning process (Ahmadi, 2018;Haswani, 2014).…”
Section: Theoretical Framework and Literature Reviewmentioning
confidence: 99%
“…One of the possible factors is teachers' understanding toward the use of mobile technology in reading is very low as stated in the result of the questionnaire. Teachers' ability in operating technology becomes another crucial factor toward the absence of technology in the classroom (Haswani, 2014).…”
Section: Need Analysismentioning
confidence: 99%